CircFOXK2 promotes hepatocellular carcinoma progression and leads to a poor clinical prognosis via regulating the Warburg effect - Zheng, Jun; Yan, Xijing; Lu, Tongyu; Song, Wen; Li, Yang; Liang, Jinliang; Zhang, Jiebin; Cai, Jianye; Sui, Xin; Xiao, Jiaqi; Chen, Haitian; Chen, Guihua; et al. (Journal of experimental & clinical cancer research, 2023)
The Warburg effect is well-established to be essential for tumor progression and accounts for the poor clinical outcomes of hepatocellular carcinoma (HCC) patients. An increasing body of literature suggests that circular RNAs (circRNAs) are important regulators for HCC. However, few circRNAs involved in the Warburg effect of HCC have hitherto been investigated. Herein, we aimed to explore the contribution of circFOXK2 to glucose metabolism reprogramming in HCC. In the present study, different primers were designed to identify 14 circRNAs originating from the FOXK2 gene, and their differential expression between HCC and adjacent liver tissues was screened. Ultimately, circFOXK2 (hsa_circ_0000817) was selected for further research. Next, the clinical significance of circFOXK2 was evaluated. We then assessed the pro-oncogenic activity of circFOXK2 and its impact on the Warburg effect in both HCC cell lines and animal xenografts. Finally, the molecular mechanisms of how circFOXK2 regulates the Warburg effect of HCC were explored. CircFOXK2 was aberrantly upregulated in HCC tissues and positively correlated with poor clinical outcomes in patients that underwent radical hepatectomy. Silencing of circFOXK2 significantly suppressed HCC progression both in vitro and in vivo. Mechanistically, circFOXK2 upregulated the expression of protein FOXK2-142aa to promote LDHA phosphorylation and led to mitochondrial fission by regulating the miR-484/Fis1 pathway, ultimately activating the Warburg effect in HCC. CircFOXK2 is a prognostic biomarker of HCC that promotes the Warburg effect by promoting the expression of proteins and miRNA sponges that lead to tumor progression. Overall, circFOXK2 has huge prospects as a potential therapeutic target for patients with HCC.